The Cultural Habits and Traditions During Pregnancy and After Childbirth of the Banjar Tribe in South Kalimantan: Semi-Qualitative Descriptive - Palimbo, Adriana; Sari, Anggrita; Mahdiyah, Dede; Sogi S. Redjeki, Dwi (KnE Social Sciences, 2023)
Inequality is reflected in the high differences in maternal mortality rates in several countries. Health information is often inaccessible for some communities because the differences in the needs of different women and their families were not accounted for. This becomes a communication barrier between healthcare providers and families in selecting and making emergency decisions that may arise during pregnancy, childbirth, and postpartum. This study aimed to describe the habits and traditions of women during pregnancy and after birth in maternal health care. The method used is the descriptive semi-qualitative method with a case study approach. The research sample consisted of four Banjarese postpartum mothers with no complications from the third trimester of pregnancy until delivery. The results showed that the four research subjects carried out the prevailing traditional customs, including self-perception, services received from officers, places, and types of care, taboos about food and medicine, advice on food and medicine and rituals of safety ceremonies and prayers together with maternal health services from midwives and nurses. The findings of our study confirmed that the Banjar people are accustomed to using cultural traditions that apply to their families and communities, including who makes decisions about what health services and which facilities they need as long as they are available and affordable in the area. Keywords: Culture and Habits, Pregnancy and Childbirth, Banjarese Tribe